Fructooligosaccharides as molecular markers of geographic origin, growing region, genetic background and prebiotic potential in strawberries: A TLC, HPAEC-PAD and FTIR study - Erika Mellado-Mojica; Octavio Calvo-Gómez; Alba Estela Jofre-Garfias; Pedro Antonio Dávalos-González; Yves Desjardins; Mercedes G. López (Food Chemistry Advances, 2022)
Strawberries are one of the most consumed fruits worldwide. Scientific research has revealed unique nutraceutical properties, mainly steaming from their content of polyphenols and fructooligosaccharides (FOS), well known prebiotics. Here, we report the fingerprint (chemical composition) of strawberries as molecular markers of geographical origin, growing region, and genetic background, after analyzing different strawberry varieties grown and collected in Mexico and Canada by thin layer chromatography (TLC), high-performance anion-exchange chromatography with pulsed amperometric detection (HPAEC-PAD), and Fourier-transform infrared spectroscopy – principal component analysis (FTIR-PCA). The most abundant carbohydrates in all cases were glucose and fructose. The highest levels of sucrose were observed in Canada-grown strawberries, while Mexico-grown varieties presented the highest FOS abundance. There were clear and distinct patterns correlating FOS isomers determined by HPAEC-PAD and geographic origin. FTIR-PCA second derivative spectra also allowed the classification and differentiation of all strawberry varieties grown in both countries. We suggest that carbohydrates fingerprinting could be associated to specific environmental growing conditions, and not only to genetic makeup.